MODELING THE PROCESS OF DEVELOPING MANAGERIAL COMPETENCE - Akmalova, D.T. (SCIENCE and SOCIETY, 2025)
The study identifies basic factors for the development of organizational and managerial competence among educators: scientific rigor, purposefulness, optimality, comprehensiveness, and controllability. Adherence to these factors enhances pedagogical practice. Particular attention is given to the importance of organizational and managerial skills for educator-managers, their role in optimizing educational processes, and improving the quality of education.